Alienating The Working Class: A Social Class Discrimination in Donna Tartt’s "The Secret History" - Trikarinaputri, Ervana; Sachmadi, Ida Farida; Krishnapatria, Kriswanda (Serat: Journal of Literary & Cultural Studies, 2024)
This research aims to show how the issue of alienation is portrayed and classified in Donna Tartt’s novel The Secret History (1992). The issue of alienation in this research refers to the concept of alienation in literature that was established by Mary Horton, Nancy Gray Diaz, and Jennifer McClinton-Temple. In this research, the concept of alienation in the novel is analysed through the narrative aspects of focalization and space based on Mieke Bal’s theory of narratology. Through the narrative strategy in the novel, the main character—portrayed as the working class—who also serves as the focalizor as well as narrator is presented to express his sense of isolation and disconnection from his surroundings. This research concludes that due to his social class, the main character in the novel is presented to be alienated from his closer connections, his physical environment, and his epoch. Therefore, we argue that the portrayal of alienation in the novel represents a social class discrimination.